Distance learning for design students: an analysis of student performance in independent landscape design / Nur Huzeima Mohd Hussain ... [et al.] - Mohd Hussain, Nur Huzeima; Ahmad, Suriati; Md Sakip, Siti Rasidah; Ilias, Nur Hanim; Mansor, Azran; Bahaluddin, Azrul (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
Independent Landscape Design (LDA350) is the final semester course that requires a full landscape design proposal. This design-based syllabus is more acquainted with face to face or physical teaching-learning process. However, in order to pursuit the IR 4.0 education, this course has adopted MOOCLAA350 to engage and equip these design students with significant understanding, graphic presentation skills as well as technical aspect related to design developments and constructions. The teaching and learning environment have subsequently expanded. With the outbreak of the Covid-19 pandemic that started early this year, this course is easily adaptable to this educational change with ODL (Open Distance Learning) being the new strategy that was put forth for teaching and learning. This paper analyses student performance in adopting MOOC and ODL during the Covid-19 outbreak. An online survey supported by a comparative analysis in between the semester was conducted to evaluate the student's readiness, challenges, and performance throughout the semester. Some tools and techniques to ensure the continuity of learning during the current pandemic are described. The findings revealed factors contributing to student performance and the reality behind the success of this new teaching strategy.